Henna Tattoo: From Cosmetic Purposes to Dermatological Reactions - Mohammed Abu El-Hamd; Soha Aboeldahab (Wolters Kluwer Medknow Publications, 2024)
Introduction: Henna, commonly used as a hair dye, is also used for temporary tattoos. It is commonly mixed with para-phenylenediamine (PPD) to enhance color intensity, which may induce cutaneous sensitization. Aim: This study aimed to describe the clinicodemographic features of patients with dermatological reactions to henna tattoos. Materials and Methods: This cross-sectional study, included patients with dermatological reactions to henna tattoos. All the patients were subjected to entire medical history including clinicodemographic data and general and dermatological examinations. Results: This study included 17 female patients with a mean age of 26.88 ± 6.6 years. Of these 17 patients; 41.2% were suburban residents, 58.8% were housewives, 70.6% were married, and 47.1% were middle socioeconomic class and 53% had type IV Fitzpatrick skin. All used black color and commercial henna for cosmetic purposes, 41.2% used market henna, and 35.3% used coiffeur henna. Many (70.6%) had localized reactions with 23.5% presenting with reaction of hands, 64.7% had acute eczematous reactions, and all had a progressive course. The mean duration of the reaction was 6.76 ± 2.6 days. The mean latency time of the reaction was 2.7 ± 0.85 days. Conclusion: This study concluded that public awareness of possible cutaneous reactions to henna tattoos should be increased. The health authority legislation should control the use of black henna to minimize the consequences.